Peningkatan Hasil Belajar Matematika melalui Penerapan Model Problem Based Learning (PBL) dengan Pendekatan Teaching at the Right Level (TaRL) Kelas IV SD Negeri 1 Sumber Cirebon - Yunita Tiara Dewi; Andi Ali Kisai; Hety Mariyanah (Mataram University, 2026)
This study aims to improve the mathematics learning outcomes of fourth-grade students at SD Negeri 1 Sumber Cirebon through the implementation of the Problem Based Learning (PBL) model combined with the Teaching at the Right Level (TaRL) approach. The background of this research is the low level of students’ understanding and achievement in learning mathematics, particularly in calculating volume using standard and non-standard units, as well as the diverse cognitive ability levels within the same classroom. The method employed was Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The results indicate that the implementation of the PBL model integrated with the TaRL approach effectively enhanced students’ learning engagement and achievement. Learning mastery improved from 42% in the pre-cycle to 89% at the end of the second cycle. This approach also fostered greater self-confidence, independence, and critical thinking skills in solving contextual problems. Based on these findings, the combination of the PBL model and the TaRL approach is recommended for mathematics instruction in elementary schools, particularly for topics requiring concrete conceptual understanding.